1997
DOI: 10.1002/(sici)1097-4644(19970315)64:4<632::aid-jcb11>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proteoglycan modification on mineral formation in a differentiating chick limb-bud mesenchymal cell culture system

Abstract: In the presence of 4 mM inorganic phosphate, differentiating chick limb-bud mesenchymal cells plated in micromass cultures form a mineralized matrix resembling that of chick calcified cartilage. To test the hypothesis that cartilage proteoglycans are inhibitors of cell mediated mineralization, the synthesis, content, and turnover of proteoglycans were altered in this system, and the extent of mineralization and properties of the mineral crystals examined. In all cases where the proteoglycan synthesis or proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…As previously reported [18][19][20][21][22][23][24][25][26], the mesenchymal cells differentiated in culture and formed alcian blue positive chondrocyte nodules. At day 14 (figure 1a), the cultures began to show trace amounts of von Kossa positive staining.…”
Section: Characterization Of Culturessupporting
confidence: 82%
See 3 more Smart Citations
“…As previously reported [18][19][20][21][22][23][24][25][26], the mesenchymal cells differentiated in culture and formed alcian blue positive chondrocyte nodules. At day 14 (figure 1a), the cultures began to show trace amounts of von Kossa positive staining.…”
Section: Characterization Of Culturessupporting
confidence: 82%
“…Chick limb-bud mesenchymal cells plated in high-density micromass cultures differentiate to form a mineralizable matrix that resembles the growth plate in the chick [18][19][20][21][22][23][24][25][26]. Our earlier studies using 2,3-diphosphoglycerate and heparin, both non-specific inhibitors of CK2, showed inhibition of mineralization when protein phosphorylation was blocked [18].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The utility of FTIR microspectroscopy in studying mineralized tissues is well established (33)(34)(35)(36). The technique combines histology-like spatial localization with the quantitative capability of bulk chemical analysis and it is used routinely in such specimens to assess the spatial distribution of mineral and collagen (from the phosphate and amide peaks, respectively) (37,38).…”
Section: Introductionmentioning
confidence: 99%